Online teaching experiences during a global crisis: Private school teachers’ narratives in the Emirates - Lemana II, Henry E.; Torres, John Rey L.; Cabiling, Karla Jane P.; Ahmad, Crizjale V. (Future Science / FSH-PH Publications, 2023)
The educational sector, like many other aspects of human life worldwide, has faced unparalleled challenges due to the COVID-19 pandemic. This study investigated the perspectives of conveniently selected secondary school teachers at a private school in the United Arab Emirates regarding the transition from in-person to online teaching, aiming to enhance the effectiveness of online learning. Employing a qualitative-descriptive design, the study generated findings that revealed that utilizing diverse teaching strategies and creating interactive online learning environments promoted student engagement. Moreover, teachers established a friendly and secure online classroom where students were encouraged to actively participate and share their thoughts on the subject matter. However, several challenges were identified, including technological difficulties, low student engagement, academic dishonesty, and feelings of isolation resulting from a lack of peer interaction, all of which significantly impacted the well-being of the participants. Despite these obstacles, teachers remained committed to their profession and maintained a passion for supporting their families. The study recommends encouraging teachers to continue integrating technology into the teaching and learning process, embracing innovative methodologies, and providing logistical and psychological support to effectively navigate the challenges posed by educational disruptions. Findings also provide a significant backdrop for the improvement of the implementation and effectiveness of digital education.